Mecanismos utilizados para monitorear el poder de mercado en mercados eléctricos: reflexiones para Colombia. (2012)
The objective of this paper is to investigate the viability of using the Residual Supply Index (RSI) in the Colombian electrical pool, in order to promote market competition. We base our evaluation on a literature review of the international experiences related to the monitoring mechanisms of the power market and an analysis of the Document CREG 118 from the Commission for the Regulation of Energy and Gas (CREG). According to international evidence, the main conclusion from this review is that the development of long-run markets has been very favourable. However, the RSI is not a good control mechanism in hydraulic markets.